Characterization of Thin MAPb(I1–xBrx)3 Alloy Halide Perovskite Films Prepared by Sequential Physical Vapor Deposition - Fru, Juvet Nche; Nombona, Nolwazi; Diale, Mmantsae (Frontiers in Energy Research, 2021)
Lead iodide (PbI2)-rich methylammonium lead bromide-iodide (MAPb(I1-xBrx)3) thin-films for solar cells were prepared by sequential physical vapor deposition of methylammonium lead tri-bromide (MAPbBr3) on methylammonium lead tri-iodide (MAPbI3) bottom layer. The structural, optical, morphology, and electrical properties of the thin-films were studied as the thickness of methylammonium bromide (MABr) in the MAPbBr3 was increased from 300 to 500 nm. The X-ray diffractograms confirmed that tetragonal MAPbI3 is transformed to a cubic-like MAPbBr3 structure phase of MAPb(I1-xBrx)3 (x= 0.89-0.95) and with PbI2 formed alongside. UV-Vis absorption spectra showed that the bandgap of the thin-film alloy decreases from 2.21 to 2.14 eV as the thickness of MABr is increased. Scanning electron micrographs depicted densely packed grains that entirely covered the substrate. The average grain size increased from 150 to 320 nm as the thickness of MABr increased. Electrical properties showed high charge carrier mobility that increased linearly with MABr thickness. FTO/MAPb(I1-xBrx)3/Au devices with fluorine-doped tin oxide (FTO) as substrate and gold (Au) as contacts were fabricated and used for the determination of the charge carrier mobility and trap density of MAPb(I1-xBrx)3 using the space charge limited current theory. The charge carrier mobility was observed to increase linearly with the thickness of MABr. Devices using titanium dioxide compact (c-TiO2) and mesoporous (m-TiO2) layers as electron transport layers were also fabricated for the application of Mott-Shottky (M-S) theory. Analyses of dark current-voltage and capacitance-voltage curves of FTO/c-TiO2/m-TiO2/MAPb(I0.11Br0.89)3 solar cells revealed a sizeable built-in voltage (Vbi) of 1.6 V and an accumulation of charge at interfaces for voltages greater than 0.2 V, respectively. Similar analyses for FTO/TiO2/MAPbI3/Au showed a small Vbi of 0.7 V and no charge carrier at interfaces. The work paves a way for reproducible growth of MAPb(I1-xBrx)3 and sheds more light on the degree of ion migration in mixed halide and pure halide perovskites.